Overweight, Obesity, and Lifestyle Practices among Urban Market Adults in Douala, Cameroon: A Cross-Sectional Study with SDG Implications - Chioma, Beauty Elee; Nguefack, Ulrich Herlick Zeuton; Akrukem, Brenda Fon; Chioma, Precious Ubah; Chidubem, Happiness Amamchukwu; Ihuoma, Blessing Ubochi; Meh, Basil Kum (European Scientific Journal, ESJ, 2026)
Background: Overweight and obesity represent a major public health crisis in urban sub-Saharan Africa. Cameroon records high urban overweight and obesity rates, yet empirical data specifically characterising lifestyle practices in high-risk urban commercial settings remain scarce. Objective: To assess lifestyle modification practices and body mass index (BMI) categories among adults at Marché Tankho, Bonaberi, Douala, and to discuss implications for the Sustainable Development Goals (SDGs). Materials and Methods: A descriptive cross-sectional study was conducted among 530 adults recruited by convenience sampling. Anthropometric measurements were obtained and BMI calculated per WHO (2024) criteria. A structured, bilingual, pre-tested questionnaire assessed dietary habits, physical activity, and sedentary behaviour. Data were analysed using IBM SPSS v26.0 and presented as frequencies and percentages. Results: Most respondents (38.9%) were aged 26–35 years; 71.5% were female; 47.5% had tertiary education. The combined overweight and obesity prevalence was 54.7% (overweight 42.1%; obesity 12.6%). Regular consumption of sugary drinks was reported by 70.9%, late-night eating by 64.7%, and fast food intake ≥3–4 times per week by 39.4%. Although 78.1% reported regular exercise, sedentary behaviour was high: 42.3% sat for 4–6 hours daily and 53.8% used motorised transport for short distances. Only 36.0% demonstrated good overall dietary practices. Conclusion: Overweight and obesity are highly prevalent at Marché Tankho, driven by a significant knowledge-practice gap in lifestyle modification. Multi-component, community-level interventions integrating nursing health promotion, physiotherapy-guided physical activity programming, and public health policy are urgently needed.